Adverse Effects Associated With Currently Commonly Used Antifungal Agents: A Network Meta-Analysis and Systematic Review - Yang, Yan-Li; Xiang, Zi-Jian; Yang, Jing-Hua; Wang, Wen-Jie; Xu, Zhi-Chun; Xiang, Ruo-Lan (Frontiers in Pharmacology, 2021)
Background: Invasive fungal infections (IFI) is an important contributing factor in morbidity and mortality of immunocompromised and critically ill patients. Although the therapeutic effects of these drugs on IFI have been well documented, the long-term use of antifungal agents has raised concerns about drug tolerability and treatment-related toxicity risks. Methods: We searched articles published before June 30, 2020 in four electronic databases: Web of Science, Cochrane Library, EMBASE and PubMed. Results: 66 trials were determined to meet our inclusion criteria, providing data on 18,230 participants. We sorted out 23 AEs by system organ classes and six laboratory AEs, 13 of these were used to construct 13 network meta-analyses. Compared with LAmB, anidulafungin, caspofungin, micafungin, fluconazole, and posaconazole had a significantly low incidence of discontinuation of therapy due to AEs (OR = 0.24 (0.09,0.65), 0.24 (0.13,0.43), 0.32 (0.19,0.52), 0.38 (0.23,0.62) and 0.35 (0.17,0.69), respectively). Conclusions: We found that echinocandins are the most tolerated antifungal agents with high safety. The AEs of triazole drugs are mainly concentrated on the increase in liver enzymes, nervous system disorders, especially visual disorders, gastrointestinal disorders, and cardiac diseases. LAmB is the least tolerated and has the most abundant AEs.